Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The following expression is given: $$\frac{x^7+y^7+z^7}{xyz(x^4+y^4+z^4)}$$

Simplify it, knowing that $x+y+z=0$.

share|improve this question
    
Use that $z=-(x+y)$ and substitute and suffer for a bit. I think you should get a nice answer :) –  Daniel Montealegre Mar 2 '12 at 2:04
    
@Victor: Diophantine equations? There is no equation and $x,y,z$ can be real/complex. contest-math? How do you know? I am removing those tags. –  Aryabhata Mar 2 '12 at 5:04

4 Answers 4

Use that $z=-(x+y)$, so you have that the numerator turns out to be $$x^7+y^7-(x+y)^7=-7x^6y-21x^5y^2-35x^4y^3-35x^3y^4-21x^2y^5-7xy^6$$Also, the denominator turns out to be $$xy(-x-y)(x^4+y^4+(-x-y))^4=-2x^6y-6x^5y^2-10x^4y^3-10x^3y^4-6x^2t^5-2xy^6$$You can factor a $7$ from the numerator and a $2$ from the denominator, and the answer turns out to be $$\frac{7}{2}$$

share|improve this answer
    
Thanks a lot. , I was trying to set a,b,c as the roots of a third degree polynomial , but that'd be much harder. –  Felipe Mar 2 '12 at 2:21

Note: Using Newton's identities, we can calculate the below expressions more easily, following the easy recursive definition.

But, your idea of writing as roots of third degree polynomial works I believe, but requires some work and we show that here:

Let $\displaystyle x,y,z$ be roots of $\displaystyle t^3 + at - b = 0$. We have that $\displaystyle a = xy+yz+zx$ and $\displaystyle b = xyz$.

Since $\displaystyle t^3 = b - at$, multiply by $\displaystyle t^4$ we get $\displaystyle t^7= bt^4 - a t^5$.

Setting $\displaystyle t=x,y,z$ in turn and adding gives us

$\displaystyle x^7 + y^7 + z^7 = b(x^4 + y^4 + z^4) - a(x^5 + y^5 + z^5)$

Similar to above, we get $\displaystyle t^5 = bt^2 - a t^3$, setting $\displaystyle t=x,y,z$ and adding gives us

$\displaystyle x^5 + y^5 + z^5 = b(x^2 + y^2 + z^2) - a(x^2 + y^3 + z^3)$.

Similarly we get

$\displaystyle x^3 + y^3 + z^3 = 3b$

We also have $\displaystyle (x+y+z)^2 = 0$, giving us

$\displaystyle x^2 + y^2 + z^2 = -2a$.

Thus

$\displaystyle x^5 + y^5 + z^5 = -2ab - 3ab = -5ab$.

Now $\displaystyle t^4 = bt - at^2$ and in a similar fashion we get

$\displaystyle x^4 + y^4 + z^4 = -a(x^2+y^2 +z^2) = 2a^2$

Thus $\displaystyle xyz(x^4 + y^4 + z^4) = 2a^2 b$

and $\displaystyle x^7 + y^7 + z^7 = 2a^2b - (-5a^2b) = 7a^2 b$.

Thus the given expression is $\displaystyle \frac{7}{2}$.

This approach can be used to generate identities.

For instance, show that

$\displaystyle 10(x^7 + y^7 + z^7) = 7(x^2 + y^2 + z^2)(x^5 + y^5 + z^5)$

share|improve this answer

Exploit the innate symmetry! Using Newton's identities to rewrite the power sums as elementary symmetric functions is very simple because $\rm\:e_1 = x+y+z = 0\:$ kills many terms.

Write $\rm\ \ c = e_2 = xy + yz + zx,\ \ \ d = e_3 = xyz,\ \ \ p_k =\: x^k + y^k + z^k.$

$\rm\qquad\qquad p_1\ =\ e_1 = 0$
$\rm\qquad\qquad p_2\ = {-}2\: c$
$\rm\qquad\qquad p_3\ =\ \ \ 3\: d$
$\rm\qquad\qquad p_4\ = - c\: p_2\ =\ 2\: c^2$
$\rm\qquad\qquad p_5\ = -c\: p_3 +\: d\: p_2\ = {-}5\: c\: d$
$\rm\qquad\qquad p_7\ = -c\: p_5 +\: d\: p_4\ =\ 7\: c^2 d$

Hence $\rm\displaystyle\ \frac{p_7}{p_4 d}\: =\: \frac{7\: c^2\: d}{2\: c^2\: d}\: =\: \frac{7}{2}$

share|improve this answer
    
I did mention that in my answer, but +1 for showing it here. –  Aryabhata Mar 2 '12 at 5:45
    
@Aryabhata I hadn't refreshed the page, so I didn't see your latest edit. In any case, it is probably helpful to some readers to see the details. –  Bill Dubuque Mar 2 '12 at 7:23
1  
Newton's identities is indeed very helpful –  Lorenz Chaos Mar 2 '12 at 9:45

First $(x^3 + y^3 +z^3)(x+y+z) = x^4 + y^4 + z^4 + xy^3 + yx^3 + xz^3 +zx^3 +yz^3+y^3z = 0 $ which means

$$ x^4 + y^4 + z^4 = -xy(x^2+y^2) - yz(y^2+z^2) -zx (z^2 + x^2) \ \ \text{(1)}$$
$x+y+z=0$ also implies $x^2+y^2=z^2-2xy$, substitute all the sum of square we have $ x^4 + y^4 + z^4 = -xy(z^2-2xy) - yz(x^2-2xz)-zx(y^2-2zx)=-xyz(x+y+z)+2(x^2y^2+y^2z^2+z^2x^2) $

So $$ x^4 + y^4 + z^4=2(x^2y^2+y^2z^2+z^2x^2) \ \ \text{(2)}$$

Next consider $ x^3+y^3-(x+y)^3 = -3xy(x+y) $ (this is a basic identity) So we have $ x^3 + y^3 +z^3 = 3xyz $ for $x+y+z = 0$
$3xyz(x^4+y^4+z^4)=(x^3 + y^3 +z^3)((x^4 + y^4 +z^4)=x^7+y^7+z^7+ x^4y^3 + y^4x^3 + x^4z^3 +z^4x^3 +y^4z^3+y^3z^4 = x^7+y^7+z^7 +x^3y^3(x+y)+y^3z^3(y+z)+z^3x^3(z+x)$

By substitution with $\text{(1)}$ and $\text{(2)}$,

$$3xyz(x^4+y^4+z^4) =x^7+y^7+z^7-xyz(x^4+y^4+z^4)/2 $$

Therefore the fraction is $\frac{7}{2}$

Wow it's not this long in my thought.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.